2019
DOI: 10.1039/c9bm00128j
|View full text |Cite
|
Sign up to set email alerts
|

Nature-inspired extracellular matrix coating produced by micro-patterned smooth muscle and endothelial cells endows cardiovascular materials with better biocompatibility

Abstract: Functionalizing cardiovascular biomaterials with an extracellular matrix (ECM) via in vitro decellularization has been applied as an effective method to improve the biocompatibility of implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 48 publications
0
35
0
Order By: Relevance
“…The surface biochemistry and biophysical characteristics of biomaterial scaffold are the key factors of cell adhesion, growth, proliferation and differentiation [ 3 , 17 , 23 ]. For example, ECM stiffness can regulate the integrity, permeability and leukocyte migration of vascular EC monolayers [ 12 , 23 , 25 , 38 , 39 ]. Moreover, controlling nanotopography and mechanical properties can be used to stimulate cells by mimicking their natural environment, triggering the correct functionalities [ 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface biochemistry and biophysical characteristics of biomaterial scaffold are the key factors of cell adhesion, growth, proliferation and differentiation [ 3 , 17 , 23 ]. For example, ECM stiffness can regulate the integrity, permeability and leukocyte migration of vascular EC monolayers [ 12 , 23 , 25 , 38 , 39 ]. Moreover, controlling nanotopography and mechanical properties can be used to stimulate cells by mimicking their natural environment, triggering the correct functionalities [ 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that hyaluronic acid (HA) has double functionality as anticoagulant and promoter of endothelialization [ 21 , 22 , 23 ]. HA, as a unique glycosaminoglycan, widely exists in the ECM of various tissues [ 10 , 24 , 25 ]. It has been recognized that HA plays a key role in adjusting biological functions by binding to specific protein receptors (such as CD44) on different cell surfaces [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…ECs were inoculated into 24-well plates at a density of 1.5 × 10 3 cells and cultured in the same way as above. Finally, the cells stained by AO/EB double-staining kit (Solabio) were observed by laser confocal microscopy (Nikon C2 Plus, Tokyo, Japan) 32…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the cells stained by AO/EB double-staining kit (Solabio) were observed by laser confocal microscopy (Nikon C2 Plus, Tokyo, Japan). 32…”
Section: Ao/eb Staining Of Ecsmentioning
confidence: 99%
“…Human umbilical vein endothelial cells (HUVEC, purchased from Chengdu Hao Yi Biotechnology Co., Ltd., Chengdu, China) ranged from the third to the fifth passages were seeded on the 6-well plate with concentration of 7 × 10 3 cells/well, and cultured with the 1640 medium containing MgNPs, MgNPb, HA/PEIs (small size), HA/ PEIb (big size) and the pure MgCl 2 at 37°C, with 5% CO 2 [29]. After incubated for 1, 6, 12 h, 1 day, 3 days and 5 days, the HUVEC were cleaned with phosphate buffer solution (PBS, pH 7.4) and fixed with 4% paraformaldehyde [30]. The fixed HUVEC were fluorescence-stained with CD31 antibody (Sigma, USA) and 4, 6-diamino-2-phenyl indole (DAPI, Sigma, USA), and recorded by a fluorescence microscope (DMRX, Leica, Germany) [19].…”
Section: Endothelial Functional Testsmentioning
confidence: 99%